(3EOGQI GdeYQaIs - (3QHMj eUWai(B, (3YdjGfs ((3YeGf(B:s (3OGQ UaGA(B,s, 2007)
(3eONd Gdi GdGOGQI, gQejI GdeYQaI, GdeYQaI GfhGYgG hNUGFUgG, GOGQI GdeYQaI, YedjGJ GOGQI GdeYQaI hfeGPLgG, fXe GdeYdheGJ GdGOGQjI hGOGQI GdeYQaI, eLJeY GdeYdheGJ heLJeY GdeYQaI hGdhGbY GdYQHj, GbJUGO GdeYQaI, ChYjI GdeYQaI, eTcdGJ GOGQI GdeYQaIs
(3HHdjhZQGajG(B: (3U(B. 461s
Keywords: (3GdGOGQIs; (3GdGbJUGOs; (3GdeYQaIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s